(untitled) (Fiep Bulletin - online, 2013)
This paper is a new reality in the educational scenario of Brazilian graduate programs in physical education because it is a Graduate Course in Physical Education in the form of distance learning/Semi In class, offered by the State University of Ponta Grossa (UEPG) in partnership with the Open University System Program of Brazil (UAB). The course offered in vogue with three centers of cities in Parana (Congonhinhas, Lapa and Palmeira) offering 50 places available in each of the poles and the selection process will occur in the years 2009, 2010 and 2011 when the month of January. In proposing the course is unique for alternate moments of the distance education courses for moments of theoretical and practical classes for subjects with such connotations. The use of modern resources of information technology and communication, UEPG allies in the tradition of offering the course in Bachelor of Physical Education in the face mode, will provide an entire community that the most varied reasons have no access to traditional methods of teaching only presence, the opportunity to be graduating in Graduates in Physical Education.